The Impact of Global Trend on Courier Service and Consumer Satisfaction: A Study of DHL - Pandey, Rudresh; Ganatra, Varsha; Sonawane, Harsh; Binti Mohd Fauzi, Fahada Nur; Kee, Daisy Mui Hung; Binti Mohd Yasir, Nur Hafizah; Binti Suhairi, Nur Fatini Farisya; Binti Md Zamri, Nur Afeza Azila (AIBPM Publisher, 2021)
The study seeks to analyze the impact on DHL courier service as well as its customer satisfaction of global trends. The research was conducted by collecting data from the company websites, personal experiences, different theories, and some statistical details. Surveys were also carried out to gather information about its courier service and customer satisfaction. The findings showed that the pattern of logistics has a major effect on organizational and customer satisfaction.